"I Could See Little Bits of How I Progressed": Coordinating Rhythms in a Midwest Gender‐affirming Health Clinic. (22nd July 2021) - Racila, Ana‐Monica
Abstract: This article examines how staff and patients worked to reconcile the rhythms of the body with those of gender‐normative health care bureaucracy in a U.S. Midwest gender‐affirming health clinic. Drawing from observations of clinical appointments and routine bureaucratic practice, as well as debriefing interviews with transgender and gender‐expansive patients, this article applies Laura Bear's theory of "time‐maps" and a new materialist approach to bodily agency that recognizes the variability of the body's responses to gender‐affirming health care. This evidence demonstrates how health care staff and patients' labor practices structured patients' abilities to embody their plans for medical transition. Anticipating the varied trajectories bodies take during medical transition can interrupt the reproduction of harmful cultural assumptions about sex difference in U.S. health care bureaucracy.